A Child with Prostaglandin I2-associated Thyrotoxicosis: Case Report - Yuri Sonoda; Kenichiro Yamamura; Kanako Ishii; Kazuhiro Ohkubo; Kenji Ihara; Yasunari Sakai; Shouichi Ohga (Galenos Yayincilik, 2019)
Prostaglandin I2 (PGI2) causes hyperthyroidism, a critical complication in patients with pulmonary arterial hypertension (PAH). However, it remains unknown whether PGI2 may have unfavorable effects on thyroid function in children with congenital portosystemic venous shunt syndrome (CPSVS). We present a boy with CPSVS who developed PAH at seven years of age. During ongoing PGI2 therapy, he experienced thyrotoxicosis at 17 years of age. The literature review showed that the reported 12 patients with PAH (median 11 years of age) developed hyperthyroidism during between one and 11 years of PGI2 treatment. Only one patient survived the acute PAH crisis due to hyperthyroidism. These data provide evidence that prophylactic intervention for hyperthyroidism is indicated for children with CPSVS during PGI2 treatment.